Efficacy and Safety of Carotid Endarterectomy Versus Carotid Artery Stenting in Asymptomatic Severe Carotid Stenosis:: A Systematic Review and Meta-Analysis (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Internal Medicine; Research